Investigation of liquid cooling on M9506A high density Keysight AXIE chassis - Gilvey, Zachary Howard, author; Bandhauer, Todd M., advisor; Marchese, Anthony, committee member; Simske, Steve, committee member (Colorado State University. Libraries, 2021)
Forced convection air-cooled heat sinks are the dominant cooling method used in the electronics industry, accounting for 86% of high-density cooling in data centers. However, the continual performance increases of electronics equipment are pushing these air-cooled methods to their limit. Fundamental limitations such as acoustics, cooling power consumption, and heat transfer coefficient are being reached while processor power consumption is steadily rising. In this study, a 4U, 5-slot, high density computing box is studied to determine the maximum heat dissipation in its form factor while operating at an ambient air temperature of 50°C. Two liquid cooling technologies were analyzed in this effort and compared against current state-of-the-art air-cooled systems. A new configuration proposed using return jet impingement with dielectric fluid FC72 directly on the integrated circuit die shows up to a 44% reduction in thermal resistance as compared to current microchannel liquid cooled systems, 0.08 K W-1, vs 0.144 K W-1, respectively. In addition, at high ambient temperatures (~45°C), the radiator of the liquid cooled system accounts for two thirds of the thermal resistance from ambient to junction temperature, indicating that a larger heat exchanger outside the current form factor could increase performance further. The efficiency of the chips was modeled with efficiency predictions based on their junction temperature. On a system level, the model showed that by keeping the chassis at 25°C ambient, the overall power consumption was significantly lower by 500W. Furthermore, the failure rate was accounted for when the chip junction temperature was beyond 75°C. FC72 jet impingement on the die showed the best performance to meet the system cooling requirements and kept the chips below 75°C for the highest ambient temperatures but consumed the most pumping power of all of the fluids and configurations investigated. The configuration with microchannels bypassing TIM 2 showed near the same performance as jet impingement with water on the lid and reduced the junction temperature difference by 5°C when compared to baseline. When the fluid was switched from water to a water glycol 50/50 mixture, an additional thermal resistance of 0.010 K W-1 was recorded at the heat sink level and a higher mass flow rate was required for the GC50/50 heat exchanger to achieve its minimum thermal resistance.
Keywords: cold plate; high performance cooling; microchannels; heat sink; advanced electronics cooling; jet impingement